Polaron in TiO2 from First‐Principles: A Review. Issue 2 (11th November 2021) - De Lile, Jeffrey Roshan; Bahadoran, Ashkan; Zhou, Su; Zhang, Jiujun
Abstract: Often the choice of semiconductor material for light‐chemical energy conversion in solar cell technology is TiO2 polymorphs. However, quantum‐mechanical phenomena of electron self‐trapping (polaron) in these polar semiconductors present a challenge to optimize their performance for absorption of solar radiation. The electron trapped in the defect site of the lattice may suppress the recombination of charge carriers and improve the efficiency of light‐chemical energy conversion. Therefore, it is crucial to study polarons in transition metal oxides and semiconductors using first‐principles methods to elucidate the nature of charge carriers and trapping sites for ameliorating the performance of energy conversion. In this work, a comprehensive review is presented using selected literature of polaron studies in TiO2 from first‐principles methods. Overview of the Landau–Pekar model to the recent development of ab initio theory of polaron is presented. The popular DFT+U approach and hybrid functional method are discussed to show the general way of studying polaron using ab initio methods. Introduction of electron‐phonon interaction and the ab initio theory of polaron are briefly presented Therefore, this review presents the development of first‐principles methods from Landau theory to the state‐of‐the‐art to study polarons using TiO2 as the toy model. Finally, conclusions and future perspectives are outlined. Abstract : Historically, from Landau–Pekar's theory to Froehlich and Holstein polaron models are used to study self‐trapping electrons and holes. Recently, ab initio description of polaron is fully treated, including electron‐phonon interactions and corrections to electron self‐energy. Therefore, this article reviews the theory and the recent progress of ab initio polaron studies.